KONTROL STRUKTUR GEOLOGI PADA ALTERASI DAN MINERALISASI DI DAERAH CIBALIUNG, KABUPATEN PANDEGLANG, PROVINSI BANTEN: CONTROL OF GEOLOGICAL STRUCTURE ON ALTERATION AND MINERALIZATION IN CIBALIUNG AREA, PANDEGLANG REGENCY, BANTEN PROVINCE - Bari, Abdul; Fatimah Rosana, Mega; Haryanto, Iyan (Buletin Sumber Daya Geologi, 2020)
Cibaliung is located in the Honje Igneous Complex, which is a Miocene volcanic complex, having two economically mineable quartz veins, i.e. Cikoneng and Cibitung veins. These veins have been mined and produced by PT Cibaliung Sumber Daya - subsidiary of PT Aneka Tambang Tbk. In the production process, the veins have reached the maximum limit. Therefore, a new reserve must significantly be discovered. The research methodology includes observation of geological structures with topographic lineament analysis, circular feature, river lineament analysis using Digital Elevation Model, and measurement of brecciation structure, shear fracture and gash fracture. The results of field data interpretation from 328 observation locations with 8,114 geological structure data both for shear fracture and gash fracture show that the presence of geological structures is directly proportional to the intensity of alteration and mineralization. From the structural and fault movement analysis and the correlation with mineralization and alteration data, there can be delineated 14 prospect areas, namely the Cikoneng-Cibitung, Cibengang, Rorah Kadal, Cikeni, Ramada, Mastar, Muara Cikeni, Cipatat, Ciburial, Cikamancing, Sompok Uara, North Batulawang, Cikarae-Cingenge, and Ciparay Prospects. From these prospects, it is recommended to conduct further exploration on six prospects, namely Cibengang, Ramada, West Cikoneng, Cikamancing, North Sompok and the North Batulawang Prospects.